Potentials and Limitations of MEO SAR - Matar, Jalal; López-Dekker, Paco; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2016)
This paper discusses the various aspects of Synthetic Aperture Radar (SAR) missions in Medium Earth Orbits (MEO). It covers the design of suitable orbits and their corresponding coverage, with emphasis on repeat ones. Furthermore, it analyses the changes in performance as altitude increases, while addressing the potentials and limitations of high orbits. Throughout the paper one interesting orbit, repeating its ground track every 3 days and providing near-global coverage, is studied.
DLR Import::2019-04-03